Proposal to classify Ralstonia solanacearum phylotype I strains as Ralstonia nicotianae sp. nov., and a genomic comparison between members of the genus Ralstonia - Liu, Jun-Ying; Zhang, Jian-Feng; Wu, Han-Lian; Chen, Zhen; Li, Shu-Ying; Li, Hong-Mei; Zhang, Cui-Ping; Zhou, Yuan-Qing; Lu, Can-Hua (Frontiers in Microbiology, 2023)
A Gram-negative, aerobic, rod-shaped, motile bacterium with multi-flagella, strain RST, was isolated from bacterial wilt of tobacco in Yuxi city of Yunnan province, China. The strain contains the major fatty acids of C16:0, summed feature 3 (C16:1ω7c and/or C16:1ω6c), and summed feature 8 (C18:1ω7c and/or C18:1ω6c). The polar lipid profile of strain RST consists of diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, and unidentified aminophospholipid. Strain RST contains ubiquinones Q-7 and Q-8. 16S rRNA gene sequence (1,407 bp) analysis showed that strain RST is closely related to members of the genus Ralstonia and shares the highest sequence identities with R. pseudosolanacearum LMG 9673T (99.50%), R. syzygii subsp. indonesiensis LMG 27703T (99.50%), R. solanacearum LMG 2299T (99.28%), and R. syzygii subsp. celebesensis LMG 27706T (99.21%). The 16S rRNA gene sequence identities between strain RST and other members of the genus Ralstonia were below 98.00%. Genome sequencing yielded a genome size of 5.61 Mbp and a G + C content of 67.1 mol%. The genomic comparison showed average nucleotide identity (ANIb) values between strain RST and R. pseudosolanacearum LMG 9673T, R. solanacearum LMG 2299T, and R. syzygii subsp. indonesiensis UQRS 627T of 95.23, 89.43, and 91.41%, respectively, and the corresponding digital DNA–DNA hybridization (dDDH) values (yielded by formula 2) were 66.20, 44.80, and 47.50%, respectively. In addition, strains belonging to R. solanacearum phylotype I shared both ANIb and dDDH with strain RST above the species cut-off values of 96 and 70%, respectively. The ANIb and dDDH values between the genome sequences from 12 strains of R. solanacearum phylotype III (Current R. pseudosolanacearum) and those of strain RST were below the species cut-off values. Based on these data, we concluded that strains of phylotype I, including RST, represent a novel species of the genus Ralstonia, for which the name Ralstonia nicotianae sp. nov. is proposed. The type strain of Ralstonia nicotianae sp. nov. is RST (=GDMCC 1.3533T = JCM 35814T).